Pengaruh Musik Pop terhadap Kreativitas Menggambar : Indonesia - aleeza, celine; Az-Zahrah , Sarah; Shufie Fahman, Lydiana; AL-Riska, Vera (Jurnal Ilmiah Penelitian Psikologi, 2025)
This research aims to determine the influence of pop music on drawing creativity among students at the Faculty of Psychology, YARSI University. One of the phenomena underlying this research is based on the organizational college life within the researcher's internal scope, where there is a lack of creativity among organizational members in work programs over the past three years where there has been no innovation. Using the static group design experimental method, this study involved two groups, namely the experimental group who drew while listening to pop music and the control group who drew without music. Statistical analysis using the independent sample t-test. Participants in this study were students of the Faculty of Psychology, YARSI University with an age range of 18-25 years. The number of samples in this study was 10 participants. The results of the t-test study showed that there was no significant difference between the average drawing creativity scores in the control group and the experimental group with a p value = 0.442. So it can be concluded that H0 cannot be rejected or there is no significant difference between the control group and the experimental group (µ1 = μ2).